Predisposing factors of diabetic foot amputation among the diabetic patients in a tertiary care hospital - Khan, Tayyab Mumtaz; Asghar, Omar; Sadiqa, Ayesha; Mansoor, Sana; Mumtaz, Madeeha; Aslam, Ayesha; Azhar, Saad; Waheed, Aleeha; Tasleem, Abeeha (International Surgery Journal, 2022)
Background: Diabetes is one of the major health problems in the world. Along with multiple complications, one of those devastating complications, is diabetic foot and it can even lead to limb amputation. The objective of this study to recognize the risk factors for foot amputation among diabetic patients. Methods: This cross-sectional study was conducted at Sir Ganga Ram Hospital of Lahore. 268 diabetic patients were recruited through a set of inclusion and exclusion criteria. After taking informed consent from all patients, data was collected via a self-designed proforma. SPSS version 25 was used to analyze data. Chi-square was applied to identify any association. Results: From the total of 268 patients 72 (26.80%) were advised amputation, whereas, 196 (73.20%) patients were managed conservatively. The correlation between diabetic foot amputation and various factors which included gender (p=0.0001), educational status (p=0.0003), socioeconomic status (p=0.004), diet modification (p=0.002), blood sugar monitoring (p=0.001), life style (p=0.0003), therapy type (p=0.04), compliance with treatment (p=0.001), smoking (p=0.02), hypertension (p=0.004), ischemic heart disease (p=0.03), stroke (p=0.01), peripheral neuropathy (p=0.003), and peripheral arterial disease (p=0.001) was statistically significant, while, the correlation was not significant between diabetic foot amputation and duration of diabetes (p=0.07). Conclusions: In summary, the incidence of foot amputation among diabetic patients is quite high. The factors that lead to foot amputation are male gender, lower educational status, lower socioeconomic status, no diet modification, no blood sugar monitoring, sedentary life style, inappropriate therapy, poor compliance, history of smoking, hypertension, ischemic heart disease, stroke, peripheral neuropathy, and peripheral arterial disease.